Marine stepping‐stones: Connectivity of Mytilus edulis populations between offshore energy installations. Issue 4 (11th February 2020) - Coolen, Joop W. P.; Boon, Arjen R.; Crooijmans, Richard; van Pelt, Hilde; Kleissen, Frank; Gerla, Daan; Beermann, Jan; Birchenough, Silvana N. R.; Becking, Leontine E.; Luttikhuizen, Pieternella C.
Abstract: Recent papers have suggested that epifaunal organisms use artificial structures as stepping‐stones to spread to areas that are too distant to reach in a single generation. With thousands of artificial structures present in the North Sea, we test the hypothesis that these structures are connected by water currents and act as an interconnected reef. Population genetic structure of the blue mussel, Mytilus edulis, was expected to follow a pattern predicted by a particle tracking model (PTM). Correlation between population genetic differentiation, based on microsatellite markers, and particle exchange was tested. Specimens of M. edulis were found at each location, although the PTM indicated that locations >85 km offshore were isolated from coastal subpopulations. The fixation coefficient F ST correlated with the number of arrivals in the PTM. However, the number of effective migrants per generation as inferred from coalescent simulations did not show a strong correlation with the arriving particles. Isolation by distance analysis showed no increase in isolation with increasing distance and we did not find clear structure among the populations. The marine stepping‐stone effect is obviously important for the distribution of M. edulis in the North Sea and it may influence ecologically comparable species in a similar way. In the absence of artificial shallow hard substrates, M. edulis would be unlikely to survive in offshore North Sea waters.